A case of metachronous peripheral T‐Cell non‐Hodgkin lymphoma following chemotherapy for Hodgkin disease successfully treated with brentuximab vedotin. Issue 8 (5th May 2020) - Meconi, Federico; Provenzano, Ida; Nasso, Daniela; Mariotti, Benedetta; Pupo, Livio; Secchi, Roberto; Cerretti, Raffaella; Lucia, Anemona; Arcese, William; Cantonetti, Maria
Abstract: Occasionally, non‐Hodgkin lymphomas (NHL) occur simultaneously or subsequently to Hodgkin disease. We report on a case of a woman with Hodgkin lymphoma treated with ABVD, who developed 4 years later T‐cell NHL with both nodal and extranodal involvement. Brentuximab vedotin could be an effective choice in treating metachronous T‐cell NHL. Abstract : Occasionally, non‐Hodgkin lymphomas (NHL) occur simultaneously or subsequently to Hodgkin disease. We report on a case of a woman with Hodgkin lymphoma treated with ABVD, who developed 4 years later T‐cell NHL with both nodal and extranodal involvement. Brentuximab vedotin could be an effective choice in treating metachronous T‐cell NHL.